Projeto de segurança para museus: um estudo de caso sobre o museu de Porto Alegre Joaquim Felizardo - Machado, Elias Palminor (2014)
The presented text is the result of dissertation research for the Professional Graduation Program in Cultural Heritage of the Federal University of Santa Maria (PPGPPC / UFSM). This work will analyze the issue of security in museums, taking as a case study the Joaquim Felizardo Museum of Porto Alegre (MJF), located in the city of Porto Alegre, in the State of Rio Grande do Sul, Brazil. In order to understand the thematic focus and the cross between theoretical debates and empirical experience, researchers in the field of Cultural Heritage, Architectural Heritage and Security in Museums were used, dialoguing with several authors, such as Françoise Choay, José Luis Cardoso Zamith, Katia Beatris Rovaron Moreira, Llorenç Prats, Robert Burke, Rosaria Ono. For this study, methodologies were surveyed regarding the formulation of an Prevention and Emergency Internal Action Plan (PEIAP) and, among the analyzed plans, two have become fundamental in the design of a security instrument regarding museums: the publication" Manual de apoio à elaboração e operacionalização de Planos de Emergência de Protecção Civil"(2008), of the National Authority for Civil Protection of Portugal, and the publication "Guía para um Plan de Proteccíon de Colecciones ante Emergencias"(2008), of the Spanish Ministry of Culture. The proposed instrument was applied to the conditions presented by MJF, emphasizing the safety of people and cultural goods.